2022
DOI: 10.1007/s10597-022-00948-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Quality of Life in Relatives of Adults with Serious Mental Illness: A Systematic Review

Abstract: Caring for a family member with a serious mental illness often has an impact on the quality of life (QoL) of caregivers. This could have negative repercussions on their caring skills and thus affect the care provided to that individual. The aim of this paper is to identify current evidence on QoL factors affecting relatives of individuals suffering from serious mental illness. A systematic review related to the research question was conducted in six databases by two independent reviewers. The QoL factors of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…These findings suggest the need for holistic and family-centred care, looking not only at the person affected by the disorder's needs but also at the family caregivers, as the latter could be affected by caring and this could influence their quality of life (Lima-Rodríguez et al, 2022). Current evidence suggests that there is a need for comprehensive policies that address the family caregivers of people with different long term conditions, such as mental health disorders.…”
Section: Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest the need for holistic and family-centred care, looking not only at the person affected by the disorder's needs but also at the family caregivers, as the latter could be affected by caring and this could influence their quality of life (Lima-Rodríguez et al, 2022). Current evidence suggests that there is a need for comprehensive policies that address the family caregivers of people with different long term conditions, such as mental health disorders.…”
Section: Implications For Practicementioning
confidence: 99%
“…More support from mental health services could help caregivers to progress in their emotional trajectory towards coping and improve their caregiving knowledge and skills. This support could positively impact their quality of life, and thus improve the quality of life of the people they care for (Lima-Rodríguez et al, 2022;Zhou et al, 2021). Mental health nurses have a role in patients' and caregivers' education and in the promotion of psychological wellbeing.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…As caring becomes a more intensive time-consuming activity, carers, particularly women and those living with care recipients, may end up withdrawing entirely from the labour force or education, as well as retiring early [ 8 , 9 ]. In addition, there are well-documented impacts on carer mental and physical health and quality of life [ 10 , 11 ]. They are also at greatest risk of being lonely than non-carers [ 12 ]; loneliness itself is a risk factor for further deterioration in carer physical [ 13 ] and mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers of chronic mental patients experience a high level of anxiety, depression, insomnia, poor social interaction, stigma, and the presence of many physical diseases, which reduce the quality of life of these people (7,8). Quality of life is de ned as a person's perception of self-position in life within the framework of the culture and value system in which he lives and about his goals, expectations, standards, and concerns (9). Various studies have reported poor quality of life for CMD caregivers (6, 10).…”
Section: Introductionmentioning
confidence: 99%